Does unemployment aggravate suicide rates in South Africa? Some empirical evidence. Issue 4 (1st October 2020) - Phiri, Andrew; Mukuku, Doreen
Abstract : The purpose of our study is to investigate the cointegration relationship between suicides and unemployment in South Africa using annual data collected between 1996 and 2015. The study relies on the bounds approach to autoregressive distributive lag (ARDL) cointegration model to establish long-run and short-run cointegration between unemployment and suicide rates. Furthermore, suicide data is further disintegrated into 'sex' and 'age' demographics to provide a more disaggregated analysis. Our empirical results indicate that unemployment is insignificantly related with suicide rates with the exception for citizens above 75 years. On the other hand, other control variables such as per capita GDP, inflation and divorce appear to be more significantly related with suicides. To the best of our knowledge, this study becomes the first to investigate the time series cointegration relationship between suicides and unemployment for South Africa data.